New complexes of chelating Schiff base: Synthesis, spectral investigation, antimicrobial, and thermal behavior studies - Basim Hatim Al-Zaidi, Mohammed Mujbel Hasson, Ahmad Hussein Ismail (Journal of Applied Pharmaceutical Science, 2019)
The new bidentate Schiff base ligand (E)-1-(4-((E)-(4-(diethylamino)-2-hydroxybenzylidene)amino)phenyl)ethanone oxime HL has been synthesized via condensation of equal amounts of 1-(4-aminophenyl)ethanone oxime and 4-Diethylaminosalicylaldehyde. The title ligand characterized by using (IR, UV-Vis) spectroscopies, (1H, 13C) NMR spectra, mass spectrum, and X-ray crystallography. Chelated complexes of the prepared ligand with Co(II), Ni(II), and Cu(II) ions have been also prepared with a ratio of 1:2, M:L, and characterized by (IR, UV-Vis) spectroscopies, magnetic susceptibility, molar conductivity, and flame atomic absorption measurements. Results of spectral studies proved the chelation behavior of this ligand, which coordinated to metal ions as a monobasic N,O bidentate ligand, via imine and phenolic oxygen atom, after losing its proton. Tetrahedral geometry has been proposed for Co(II) complex and square planar geometry has been proposed for Ni(II) and Cu(II) complexes, respectively. The analysis studies of TG/DTG/DTA data reflected potential and good thermal stability of HL and its metal complexes. We also obtained the biological activity of the prepared compounds against two Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis), four Gram-negative bacteria (Salmonella, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella spp.), and one fungus (Candida albicans).
Keywords: N,O-bidentate Schiff base complexes, antibacterial, antifungal, p-aminoacetophenone oxime, TG/DTG/DTA-analysis, X-ray crystallography.